Magia, miłość, miasto. Prolegomena do źródeł popularności urban fantasy - Szymczak-Maciejczyk, Barbara (Colloquia Litteraria, 2023)
The urban fantasy genre is currently receiving increasing attention from audiences and researchers. One of the factors contributing to this is the growing reception of fantasy per se. This is also due to the recent phenomenon of paranormal romance, from which – to some extent – urban fantasy is growing and emulating. The combination of fantasy, detective and romance plots and the emphasis on urbanity allows the use of a variety of pop culture tropes and motifs. In this article, I point to these several reasons for the growing popularity of urban fantasy